Numerical simulation of Ginzburg-Landau-Langevin equations - Cassol-Seewald, N. C. [UNESP]; Krein, Gastão Inácio [UNESP] (Sociedade Brasileira de Física, 2007)
This work is concerned with non-equilibrium phenomena, with focus on the numerical simulation of the relaxation of non-conserved order parameters described by stochastic kinetic equations known as Ginzburg-Landau-Langevin (GLL) equations. We propose methods for solving numerically these type of equations, with additive and multiplicative noises. Illustrative applications of the methods are presented for different GLL equations, with emphasis on equations incorporating memory effects.
Keywords: Mon-equilibrium phenomena; Numerical simulations; Stochastic kinetic equations